Methodology of organization of individual educational and research student’s work (ERSW) (on the example of historical- legal disciplines) - Hrubinko, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article considers ways to optimize the individual work of students on the example of the proposed model of the Complex practical individual task in the discipline «History of State and Law of Foreign Countries» in accordance with the provisions of the Standard of Higher Education in specialty 081 «Law». On the basis of own teacher’s experience expediency and level of efficiency this type of individual tasks, concrete problems it introduction in an educational process are analysed.Noted that creative (heuristic) close to the scientific understanding and synthesis of the work is possible only as a result of the organization of self-study with mandatory presence goal setting and achievements through effective technological schemes of self-education. In addition, such work must be more individual according to the level of student’s creative capabilities, his academic achievements, interests, educational activity, etc. It able to implement the Complex of practical individual task (CPIT). Practical implementation of this form of individual work of students is carried out in West Ukrainian National University since 2011. The purpose of performing CPIS on the «History of State and Law of Foreign Countries» is mastering by the students the skills of research main problems and sources of development statehood and the rights of countries which are studied. The structure CPS included three tasks. The topics are arranged in chronological order. Task 1 – an independent analysis and evaluation by the student some situation or issue of concern. Task 2 – an independent analysis by the student the text of the normative act or its particular parts (individual articles or sections) and on its basis drawing up of situational tasks (incident). Task 3 – search by the student of literature to a particular topic.